2016
DOI: 10.1017/s002531541500226x
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides in green sea turtles (Chelonia mydas) with and without fibropapillomatosis caught at three feeding areas off Brazil

Abstract: Many factors threaten the survival of marine turtles, such as incidental capture by fisheries, habitat degradation, pollution and diseases. One of the most important diseases is fibropapillomatosis (FP), characterized by the development of benign skin tumours. FP predominantly affects juvenile green sea turtles (Chelonia mydas) and involves a complex multifactorial aetiology. For several years, it has been noted that the prevalence of FP tends to be higher in marine environments under the influence of human ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 62 publications
0
6
0
3
Order By: Relevance
“…Rapid visual-assessment techniques of physical condition characterization are useful in field studies of wildlife health status (Thomson et al ., 2009); however, we observed that such techniques are adequate to differentiate between regular and poor, but not between good and regular body conditions, in which the employment of BCI techniques is indicated. Preliminary studies on green turtles captured in Brazilian feeding areas revealed the same results; that the subjective assessment is reliable for individuals in poor condition but is unclear for green turtles classified as regular and good (Sánchez-Sarmiento et al ., 2012). Another study carried out in Brazil demonstrated that the subjective body condition had a good relationship with BCI when examined by a single observer, avoiding inter-observer variation (Santos et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid visual-assessment techniques of physical condition characterization are useful in field studies of wildlife health status (Thomson et al ., 2009); however, we observed that such techniques are adequate to differentiate between regular and poor, but not between good and regular body conditions, in which the employment of BCI techniques is indicated. Preliminary studies on green turtles captured in Brazilian feeding areas revealed the same results; that the subjective assessment is reliable for individuals in poor condition but is unclear for green turtles classified as regular and good (Sánchez-Sarmiento et al ., 2012). Another study carried out in Brazil demonstrated that the subjective body condition had a good relationship with BCI when examined by a single observer, avoiding inter-observer variation (Santos et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, trace elements like lead, copper, and iron have been associated with altered blood patterns and oxidative stress parameters that possibly affect the dynamics of tumor pathogeny . Conversely, no consistent pattern of organic contaminant levels was observed to explain the difference between healthy and tumor-affected C. mydas in Brazil (SANCHEZ-SARMIENTO et al, 2017). The knowledge of those concentrations is still needed to obtain a better understanding of the cause-and-effect relationships of environmental contamination and C. mydas health parameters (KOMOROSKE et al, 2011).…”
Section: Mortality and Morbidity Of Chelonia Mydas Associated With Humentioning
confidence: 99%
“…Linear regressions (Supporting Information, S9), including 95% confidence intervals, are plotted to illustrate the general trend. Data from refs and .…”
Section: Resultsmentioning
confidence: 99%